Identification of a Novel Insertion Site HVT-005/006 for the Generation of Recombinant Turkey Herpesvirus Vector - Xusheng Zai; Xusheng Zai; Xusheng Zai; Bin Shi; Bin Shi; Bin Shi; Hongxia Shao; Hongxia Shao; Hongxia Shao; Kun Qian; Kun Qian; Kun Qian; et al. (Frontiers in Microbiology, 2022)
Turkey herpesvirus (HVT) has been widely used as a successful live virus vaccine against Marek's disease (MD) in chickens for more than five decades. Increasingly, HVT is also used as a highly effective recombinant vaccine vector against multiple avian pathogens. Conventional recombination, or recombineering, techniques that involve the cloning of viral genomes and, more recently, gene editing methods have been used for the generation of recombinant HVT-based vaccines. In this study, we used NHEJ-dependent CRISPR/Cas9-based approaches to insert the mCherry cassette for the screening of the HVT genome and identifying new potential sites for the insertion of foreign genes. A novel intergenic site HVT-005/006 in the unique long (UL) region of the HVT genome was identified, and mCherry was found to be stably expressed when inserted at this site. To confirm whether this site was suitable for the insertion of other exogenous genes, haemagglutinin (HA) of the H9N2 virus was inserted into this site, and a recombinant HVT-005/006-HA was rescued. The recombinant HVT-HA can grow well and express HA protein stably, which demonstrated that HVT-005/006 is a promising site for the insertion of foreign genes.